2006
DOI: 10.4049/jimmunol.176.2.1122
|View full text |Cite
|
Sign up to set email alerts
|

Modified Pulmonary Surfactant Is a Potent Adjuvant That Stimulates the Mucosal IgA Production in Response to the Influenza Virus Antigen

Abstract: The intranasal administration of influenza hemagglutinin (HA) vaccine with Surfacten, a modified pulmonary surfactant free of antigenic c-type lectins, as a mucosal adjuvant induced the highest protective mucosal immunity in the airway. The intranasal immunization of mice with HA vaccine (0.2 μg)-Surfacten (0.2 μg) selectively induced the neutralizing anti-HA IgA, but not IgG, and conferred nearly maximal protection in the airway, without inducing a systemic response. In contrast, intranasal inoculation of vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 46 publications
0
39
0
1
Order By: Relevance
“…DDA was found equally effective as Adju-Phos when used with BBG2Na for protection against viral challenge in mice and rats [395,396]. Intranasal administration of influenza hemagglutinin (HA) vaccine with Surfacten, a modified pulmonary surfactant, induced higher protective mucosal immunity in the airway without inducing a systemic response in mice [283].…”
Section: Surfactant-like Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…DDA was found equally effective as Adju-Phos when used with BBG2Na for protection against viral challenge in mice and rats [395,396]. Intranasal administration of influenza hemagglutinin (HA) vaccine with Surfacten, a modified pulmonary surfactant, induced higher protective mucosal immunity in the airway without inducing a systemic response in mice [283].…”
Section: Surfactant-like Compoundsmentioning
confidence: 99%
“…Options to bypass their toxicities include use of subunits of toxins, toxoids, or structurally modified versions [281]. The toxin subunits could be still effective [282,283] but a less adjuvantation effect would be expected relative to the complete toxin [284]. Several non-toxic LT mutants have been recently reviewed [285].…”
Section: Toxinsmentioning
confidence: 99%
“…At days 8 and 12 after infection, nasal washes (NWs), bronchoalveolar fluids (BALF), and plasma were collected as described previously (27,45) and subjected to enzyme-linked immunosorbent assay (ELISA) to determine anti IAV-specific S-IgA and IgG levels (27,33,39). Mononuclear cells isolated from the MeLNs, lungs, NPs, and spleen were subjected to an enzyme-linked immunosorbent spot (ELISPOT) assay to determine the numbers of IgA and IgG antibody (Ab)-forming cells (AFCs), as described previously (15,17,39).…”
Section: Methodsmentioning
confidence: 99%
“…However, the toxin causes severe diarrhea and nasal discharge, so a safer and more effective adjuvant is needed for intranasal influenza virus vaccines in clinical use. Recent studies have demonstrated that synthetic double-stranded RNA polyriboinosinic acid-polyribocytidylic acid [poly(I·C)], modified pulmonary surfactant, and poly(␥-glutamic acid) nanoparticles (␥-PGA-NPs) are safe and potent candidates for use as an adjuvant in mucosal influenza virus vaccines (8,13,14). These materials induce dendritic cell (DC) activation, which plays an important role in mucosal adjuvant activity.…”
mentioning
confidence: 99%